Devanayaka panchasat of Vedanta Desika [i.e. Veṅkaṭanātha] : with meaning and commentary in English - Veṅkaṭanātha, 1268-1369 (Ayyangar, 1978)
Hymns in praise of Devanātha, form of the Hindu deity Vishnu, enshrined at Tiruvahindrapuram, Tamil Nadu.